Solve Using the Square Root Property 3x^2+7x-18=6-7x

Math
3×2+7x-18=6-7x
Move all terms containing x to the left side of the equation.
Tap for more steps…
Add 7x to both sides of the equation.
3×2+7x-18+7x=6
Add 7x and 7x.
3×2+14x-18=6
3×2+14x-18=6
Move 6 to the left side of the equation by subtracting it from both sides.
3×2+14x-18-6=0
Subtract 6 from -18.
3×2+14x-24=0
Factor by grouping.
Tap for more steps…
For a polynomial of the form ax2+bx+c, rewrite the middle term as a sum of two terms whose product is a⋅c=3⋅-24=-72 and whose sum is b=14.
Tap for more steps…
Factor 14 out of 14x.
3×2+14(x)-24=0
Rewrite 14 as -4 plus 18
3×2+(-4+18)x-24=0
Apply the distributive property.
3×2-4x+18x-24=0
3×2-4x+18x-24=0
Factor out the greatest common factor from each group.
Tap for more steps…
Group the first two terms and the last two terms.
(3×2-4x)+18x-24=0
Factor out the greatest common factor (GCF) from each group.
x(3x-4)+6(3x-4)=0
x(3x-4)+6(3x-4)=0
Factor the polynomial by factoring out the greatest common factor, 3x-4.
(3x-4)(x+6)=0
(3x-4)(x+6)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
3x-4=0
x+6=0
Set the first factor equal to 0 and solve.
Tap for more steps…
Set the first factor equal to 0.
3x-4=0
Add 4 to both sides of the equation.
3x=4
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3x=4 by 3.
3×3=43
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3×3=43
Divide x by 1.
x=43
x=43
x=43
x=43
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
x+6=0
Subtract 6 from both sides of the equation.
x=-6
x=-6
The final solution is all the values that make (3x-4)(x+6)=0 true.
x=43,-6
Solve Using the Square Root Property 3x^2+7x-18=6-7x

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top